2011
DOI: 10.21273/horttech.21.1.109
|View full text |Cite
|
Sign up to set email alerts
|

A Topical Spray to Enhance Plant Resistance to Cold Injury and Mortality

Abstract: A novel topical spray was developed to increase resistance to both cold damage and cold mortality in plant foliage, flowers, and fruits. In environmental chamber experiments, application of the spray to monocot and dicot foliage lowered the environmental temperatures associated with the first onset of cold injury and with cold mortality from 2.2 to 9.4 °F, compared with controls sprayed with tap water, over an effective temperature range (depending on species) of ≈0 to 32 °F. The threshold temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…TOMATO FRUIT. Franko et al (2011) indicated FreezePruf increased the percentage of viable tomato fruit by %50% compared with controls exposed to -3.9°C for 2 to 3.5 h. Based on that report, a preliminary experiment was conducted to determine whether the supercooling duration of tomato fruit held at -3.9°C was increased by FreezePruf. However, only one out of 40 fruit exhibited an exotherm during 24 h at -3.9°C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…TOMATO FRUIT. Franko et al (2011) indicated FreezePruf increased the percentage of viable tomato fruit by %50% compared with controls exposed to -3.9°C for 2 to 3.5 h. Based on that report, a preliminary experiment was conducted to determine whether the supercooling duration of tomato fruit held at -3.9°C was increased by FreezePruf. However, only one out of 40 fruit exhibited an exotherm during 24 h at -3.9°C.…”
Section: Resultsmentioning
confidence: 99%
“…The authors examined the effects of dimethyl sulfoxide, proline, polyvinylpyrrolidone, a mixture of amino acids, and a solution containing glycerol and vitamin E. The only treatment that increased the survival percentage after exposure to -4°C for 1 h was glycerol plus vitamin E. It was interesting to note that protection was not strictly a colligative effect since 0.7 M glycerol was optimum, but higher or lower concentrations had survival percentages that were not different from the control. Although Moratiel et al (2011) did not examine FreezePruf, glycerol (5 mM) is one of the components (Franko et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations